Exploring the Effectiveness of STEM Interdisciplinary Approach in Teaching Grade 12 Agricultural Sciences Learners - Busi Ntimane; Thabang Maphakane; Lusanda Ncisana (E-Journal of Humanities, Arts and Social Sciences)
This study explored the effectiveness of the STEM interdisciplinary approach in teaching grade 12 Agricultural Sciences learners. The study applied social constructivism theory and a qualitative approach using Phenomenology design, sampling 24 participants including 12 teachers and 12 learners through purposive in Capricorn South District, Limpopo, South Africa. Data was collected using semi-structured interviews. Results indicated that the interdisciplinary approach in STEM positively influences learner engagement and critical thinking in the retention of agricultural science concepts by relating theory to actual agricultural challenges being experienced in the real world. However, the study also identified key challenges, including resource limitations, time constraints, and teachers’ varying levels of STEM integration experience. Based on the findings of this study, modification in the curriculum is recommended to assign more time for activities with an interdisciplinary approach and invest more in resources and training of teachers to implement effectively the practice of STEM interdisciplinary approach in agricultural science education. This study contributes to scholarship by demonstrating how the STEM interdisciplinary approach enhances learner engagement and critical thinking in Agricultural Sciences. It also highlights key challenges, informing curriculum modifications, teacher training, and resource investment for effective STEM integration.